2014
DOI: 10.1021/es502291b
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution and Local Impacts of Inadvertently Generated Polychlorinated Biphenyls in Pigments

Abstract: The non-Aroclor congener 3,3'-dichlorobiphenyl (PCB 11) has been recently detected in air, water, sediment, and biota. It has been known since at least the 1970s that this congener is produced inadvertently during the production of certain organic pigments. PCB 11 was previously measured at parts-per-billion (ppb) levels in various printed materials obtained in the US. In this work, PCB 11 was detected in samples of common consumer goods including magazines, advertisements, maps, postcards, brochures, napkins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
0
42
0
1
Order By: Relevance
“…Relatively little is known about the toxicity of CB-11: as it is not substituted in the ortho-positions, it may exhibit dioxin-like toxicity (Rodenburg et al, 2010). However, measured concentrations in the Nador Lagoon are similar to those detected in other low impacted areas (Romano et al, 2013;Guo et al, 2014) and well below the limit of 50 ng g −1 set by the EU Directive 89/677/EEC for PCBs in pigments.…”
Section: Potential Toxicity Of Nador Lagoon Sediments Due To Pahs Andmentioning
confidence: 78%
“…Relatively little is known about the toxicity of CB-11: as it is not substituted in the ortho-positions, it may exhibit dioxin-like toxicity (Rodenburg et al, 2010). However, measured concentrations in the Nador Lagoon are similar to those detected in other low impacted areas (Romano et al, 2013;Guo et al, 2014) and well below the limit of 50 ng g −1 set by the EU Directive 89/677/EEC for PCBs in pigments.…”
Section: Potential Toxicity Of Nador Lagoon Sediments Due To Pahs Andmentioning
confidence: 78%
“…cable insulation, thermal insulation materials, paint, plastics, transformers, hydraulic oil; produced before the production and use of PCB was prohibited on a global scale more than 10 years ago. In addition, several studies have revealed inadvertent production of PCB congeners in the manufacturing of paint pigments (Anezaki and Nakano, 2014;Guo et al, 2014;Hu and Hornbuckle, 2009;Shang et al, 2014).…”
Section: Distribution Of Pcbmentioning
confidence: 99%
“…This investigation revealed that Portland Harbor, like the NY/NJ Harbor and the Delaware River, is impacted by PCB 11 generated inadvertently during production of organic pigments and dispersed throughout the environment by the use of such pigments in printed material, paints, etc. 26,27,29 Various data sources suggest that many other US waterways are impacted by PCBs from pigments, including the Santa Fe and Rio Grande Rivers in New Mexico (STORET), San Francisco Bay (California Environmental Data Exchange Network; http://www.ceden.org/), and the Houston Ship Canal (Houston, TX). 39 In addition, investigations in three watersheds on both the east and west coasts of the US have now found evidence of microbial dechlorination of PCBs in compartments other than sediment, including groundwater, landfills, and sewers.…”
Section: Articlementioning
confidence: 99%